PENGETAHUAN, SIKAP DAN PERILAKU KAITANNYA DENGAN MASALAH DEMAM BERDARAH DENGUE DI DAERAH PAMULANG, KABUPATEN TANGERANG, PROPINSI BANTEN - Manalu, Helper Sahat; Kasnodihardjo, Kasnodihardjo; Idris, Nur Sushanti (Media Penelitian dan Pengembangan Kesehatan, 2010)
Dengue Hemorrhagic Fever (DHF) is a disease thai still cause health problems in Indonesia. Dengue cases are still high to the understanding of a phenomenon that is not only seen from the health aspect alone, but associated with other symptoms that exist in this society means the emergence of DHF can not be separated from the low environmental quality, because public awareness to preserve the environment for mosquito vector transmission DBD does not have the opportunity to breed relatively less. Mobility is also supported by the higher population and settlements which the spread of increasingly dense and more widespread transmission of dengue. Therefore research has been done on the dynamics of dengue transmission in the area Pamulang Tangerang District, Banten Province. Research using quantitative and qualitative approaches. Kuantatif approach to collecting data through interviews using a questionnaire. The number of samples of600 people and as a respondent is the head of the family. Approach was qualitative data collection through in-depth interviews of a number of informants consisting of community leaders, religious leaders, youth, and the head of PKK health center. The results showed the public's knowledge about dengue hemorrhagic fever is good enough. Generally the respondents knew about the cause of DHF is due to Aedes aegypti mosquitoes. Symptoms and modes of transmission of DHF also well known by most respondents. They claimed that the symptoms first dengue fever, red spots dikulit, first and appetite is less. Nevertheless behavior towards the prevention of dengue transmission is still less reiatih. Most respondents claimed not implement the principle of 3M. They only carry out service projects that are less focused on the extraction of regular water and shelter is always closed, burn or bury the old stuff can be suspected of developing a mosquito biuknya dengue infection. Supported high population mobility due to frequent traveling and staying in other regions. This enables the transmission and spread of DHF in the community will take place.   Keywords: dengue transmission, social and cultural aspect